Biodegradation of Cyanuric Acid - Saldick, Jerome (1974)
Cyanuric acid biodegrades readily under a wide variety of natural conditions, and particularly well in systems of either low or zero dissolved-oxygen level, such as anaerobic activated sludge and sewage, soils, muds, and muddy streams and river waters, as well as ordinary aerated activated sludge systems with typically low (1 to 3 ppm) dissolved-oxygen levels. Degradation also proceeds in 3.5% sodium chloride solution. Consequently, there are degradation pathways widely available for breaking down cyanuric acid discharged in domestic effluents. The overall degradation reaction is merely a hydrolysis; CO(2) and ammonia are the initial hydrolytic breakdown products. Since no net oxidation occurs during this breakdown, biodegradation of cyanuric acid exerts no primary biological oxygen demand. However, eventual nitrification of the ammonia released will exert its usual biological oxygen demand.